Pengaruh Eco-Label terhadap Green Purchase - Sabilla, Rilla Umaya; Hendayani, Ratih (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
Environmental awareness is a must for everyone because environmental conditions will affect human life in the present and in the future. The purpose of this study was to determine the effect of the eco-label on green purchases through the mediating role of product attributes and environmental awareness. This research is a quantitative study. The data analysis technique in this study used SEM-PLS on SmartPLS 3.2.9 software with model measurements and hypothesis testing using the bootstrapping technique. Based on the results of data analysis, this study found that eco-label has a positive and significant effect on environmental attitudes, product attributes, and green purchases, but has no positive and significant effect on environmental concerns. Product attributes have a positive and significant effect on environmental attitudes but do not have a positive and significant effect on environmental concerns. Environmental attitudes have a positive and significant effect on environmental concerns. Environmental attitudes and environmental concerns have a positive and significant effect on green purchases. This research provides new insights and suggestions for environmentally friendly products or companies, which are based on the results of data analysis to apply environmentally friendly product labeling (eco-labels) and provide education regarding green products and environmentally friendly labels.